Pengaruh Current Ratio (CR), Return On Asset (ROA), Debt To Equity Ratio (DER), Return On Equity (ROE), Dan Earning Per Share (EPS) Terhadap Harga Saham (Studi Pada Perusahaan Asuransi Yang Terdaftar Di BEI Periode 2014-2018) - Maria Mervinsia Yupita; Silvia Indrarini (Akubis : Jurnal Akuntansi dan Bisnis, 2021)
This study aims to determine the effect of CR, ROA, DER, ROE, and EPS on stock prices in insurance companies listed on the Indonesian stock exchange for the 2014-2018 period. This type of research is explanatory research. The population in this study are insurance companies listed on the Indonesia Stock Exchange for the 2014-2018 period of 14 companies. the selected sample used purposive sampling with the criteria so that 4 companies were selected. The hypothesis was tested using the classical assumption test, F test, t test and multiple linear regression analysis. The results of this study indicate that CR, ROA, DER, ROE and EPS simultaneously affect the stock price of insurance companies. Partially CR, ROA, DER and ROE have no significant effect on stock prices, while EPS has a positive and significant effect on stock prices and the variable that has the most dominant influence on stock prices is EPS.